Kelimpahan dan Variasi Morfometrik Trichodina Sp. pada Benih Ikan Gurami (Osphronemus Gouramy Lac.) di Kolam Budidaya Desa Baji Kecematan Kedungbanteng Banyumas - Sahadian, Nurrochmah Hastia; Rokhmani, R; Riwidiharso, Edy (Universitas Muhammadiyah Surakarta, 2016)
The center one of Gurami fish hatchery is located on Kedungbanteng, Banyumas district, specially on Beji village. Trichodina sp. is a parasites that infecting the seed of gurami fish. Trichodina sp. is found in the seed of gurami fish hatchery center area with the patogenicity level for about 80 %. The gurami hatchery I is vulnerable component, because it is infecting easily by Trichodina sp. The study purposes is for determine Trichodina sp. abundance and morphometric that is infecting the gurami hatchery I at pond cultivated in Beji village. This reseach method is using survey by random sampling. Gurami seed fish sample taken from pond cultivated of gurami hatchery I in Beji village. Every sampling taken 25 fish in four times, so the calculating are 100 fish number. Reseach variable is Trichodina sp. abundance with number and morphometric parameter. That are body, denticle ring, and adhesive disc diameter, also number of denticle and width of Trichodina sp. membrane. The abundance is obtained by calculating the average number of Trichodina sp. with number of infected fish seed. Characteristic of Trichodina sp. morphometric is done by sampling technique from every infected fish seed. Morphometric variation data of Trichodina sp. analyzed descriptively. Result of this research showed that all of gurami seed are infected by Trichodina sp. All of Trichodina sp. are found as many as 5794 individual from the gurami seed infected. The total abundance of Trichodina sp. from gurami seed for about 60,35 individual and it’s relative highly. Number of Trichodina sp. morphometric measurement show the morphometric variation in body diameter in range 60-102,5 μm; 22,5-52,5 μm denticle ring diameter, 40,62-62,5 μm adhesive disc diameter, 20-26 denticle calculating, 2,5-7,5 μm membran width.